2008
DOI: 10.1007/s11430-008-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Nd isotopic compositions of the Tethyan Himalayan Sequence in southeastern Tibet

Abstract: The Himalayan orogen consists of three major lithologic units that are separated by two major north-dipping faults: the Lesser Himalayan Sequence (LHS) below the Main Central Thrust (MCT), the Greater Himalayan Crystalline Complex (GHC) above the MCT, and the Tethyan Himalayan Sequence (THS) juxtaposed by the South Tibet Detachment fault (STD) over the GHC. Due to widespread metamorphism and intense deformation, differentiating the above three lithologic units is often difficult. This problem has been overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…The accretionary prism is dominantly composed of the Triassic to Eocene sediments. However, in the eastern part of this suture, the Late Triassic Langjiexue Group is different from the strata of the accretionary prism, as these might have been derived from the Lhasa terrane to the north rather than the India to the south (Dai et al, 2008;. The Yarlung Zangbo ophiolitic belt consists of disrupted ophiolitic massifs, which represent remnants of part of Neo-Tethyan ocean lithosphere.…”
Section: Geological Settingmentioning
confidence: 97%
“…The accretionary prism is dominantly composed of the Triassic to Eocene sediments. However, in the eastern part of this suture, the Late Triassic Langjiexue Group is different from the strata of the accretionary prism, as these might have been derived from the Lhasa terrane to the north rather than the India to the south (Dai et al, 2008;. The Yarlung Zangbo ophiolitic belt consists of disrupted ophiolitic massifs, which represent remnants of part of Neo-Tethyan ocean lithosphere.…”
Section: Geological Settingmentioning
confidence: 97%
“…As the normal stratigraphic sequence was severely modifi ed by the Paleogene shortening, the South Tibetan detachment and Main Central thrust may have variable older-over-younger and younger-overolder relationships across the faults. In southern Tibet directly north of Bhutan, the South Tibetan detachment places Cretaceous strata over Greater Hima layan Crystalline Complex units (Pan et al, 2004;Dai et al, 2008), whereas in Bhutan to the south, the South Tibetan detachment places Neoproterozoic and Cambrian strata over the Greater Himalayan Crystalline Complex. This relationship suggests that the South Tibetan detachment cuts up section of its hanging-wall strata in its northward transport direction, and this relationship is inconsistent with normal-fault but consistent with thrust-fault geometry.…”
Section: Cenozoic Evolution Of the Eastern Himalayamentioning
confidence: 99%
“…However, recent studies have reported southward paleocurrent directions within the Langjiexue Group (Li et al, 2003). Whole-rock ε Nd (T) values (Dai et al, 2008) and detrital zircon ages obtained from these rocks (Aikman et al, 2008) differ from those of the Tethyan Himalaya (Gehrels et al, 2003;Hu et al, 2010) and the Xigaze forearc basin (Wu et al, 2010). This ambiguity has resulted in debate as to whether the Langjiexue Group should be assigned to the Tethyan Himalaya of the Indian plate Pan and Ding, 2004;Aikman et al, 2008), the sedimentary sequences of the Asian plate (Dai et al, 2008), or the Yarlung-Zangbo mélange (Yin, 2006;Aitchison et al, 2007a).…”
Section: Geological Settingmentioning
confidence: 99%